Pengaruh Promosi Online Menggunakan Facebook Ads Terhadap Keputusan Pembelian - Mohammad Faisal Azroi; Feti Fatimah; Yohanes Gunawan Wibowo (Universitas Muhammadiyah Jember, 2021)
The benefits of social media are not just for sharing a moment or getting information, in today's digital era, the use of social media for business activities is easy to do. Usingmedia Facebook or Instagram for business can be done easily, promotion using social media can be done with paid or free methods. The paid promotion method used in this study uses Facebook Advertising where companies can increase the reach of their wider social media interactions. The target of this research is to find the influence of Context, Communication, Collaboration, Connection on purchasing decisions at the Jember Helmet Gallery using Facebook Advertising. The sample used was purposive sampling and data collection was carried out using e-survey method. The results of the study are thevariables Context and Connection have a positive and significant effect on purchasing decisions at the Jember Helmet Gallery.